Reactive force fields for surface chemical reactions: A case study with hydrogen dissociation on Pd surfaces - Xiao, Y. (2010)
An approach based on reactive force fields is applied to the parametrization of potential energy surface (PES) for chemical reactions on surfaces with a benchmark system, H2/Pd(111). We show that a simple reactive force field based on the second moment approximation does not allow for obtaining reliable results of reaction dynamics for the considered system. With a more elaborate reactive force field, i.e., reactive bond order (REBO) force field, we succeeded in obtaining a reliable PES for H2/Pd(111). The accuracy of the constructed REBO force field is carefully checked through various tests including the comparison not only between energies calculated with density functional theory and those with REBO force field but also between the available results of ab initio molecular dynamics simulations and those with our force field. Moreover, our REBO force field is endowed with some transferability since the force field constructed with a database containing only information on H2/Pd(111) allows for obtaining also accurate results for H2/Pd(100) and qualitatively correct results for H2/Pd(110) without any refitting. With the help of our reactive force field, the molecular dynamics simulation for the dissociation of H2 on the considered Pd surfaces is speeded up by five orders of magnitude compared to ab initio molecular dynamics method. The demonstrated reliability and the very high computational efficiency of reactive force fields open extremely attractive perspectives for studying large-scale complex reacting systems.